(untitled) (The Review of Diabetic Studies, 2024)
Background: Nursing practice plays a fundamental role in shaping patient outcomes, as nurses are central to care delivery, patient monitoring, safety management, and patient education. In recent years, healthcare systems have increasingly emphasized advanced and evidence-based nursing interventions to improve clinical effectiveness, patient safety, and satisfaction. However, existing evidence on the impact of nursing interventions remains fragmented across settings and outcome measures. Objective: This systematic review aimed to synthesize current evidence on the effect of nursing interventions on patient outcomes, with a focus on clinical outcomes, patient safety, and patient satisfaction. Methods: A systematic review was conducted in accordance with the PRISMA 2020 guidelines. Electronic databases including PubMed/MEDLINE, CINAHL, Scopus, and Web of Science were searched for studies published between January 2019 and December 2024. Eligible studies examined nursing-led or nursing-related interventions and reported measurable patient outcomes. Study selection, data extraction, and quality appraisal were performed independently by two reviewers. Methodological quality was assessed using Joanna Briggs Institute (JBI) critical appraisal tools. A narrative synthesis was employed due to heterogeneity across study designs and outcome measures. Results: A total of 10 studies met the inclusion criteria. The included studies comprised randomized controlled trials, cohort studies, and quasi-experimental designs conducted across diverse healthcare settings. Nursing interventions, including advanced nursing practice, nurse-led education programs, early warning systems, and patient-centered care models, were consistently associated with improved patient outcomes. Reported benefits included reduced mortality, shorter hospital stays, lower readmission rates, fewer adverse events, and higher patient satisfaction. Overall study quality ranged from moderate to high. Conclusion: The findings of this systematic review provide strong evidence that nursing interventions significantly improve patient outcomes across clinical, safety, and satisfaction domains. These results highlight the essential contribution of nursing to healthcare quality and support the integration of advanced nursing interventions into routine practice, policy, and education.